The relationship between the value of health and health behaviors in individuals over 65 years of age - Nowicki, Grzegorz Józef; Młynarska, Magdalena; Ślusarska, Barbara; Rudnicka-Drożak, Ewa; Szczekala, Katarzyna; Bartoszek, Agnieszka (Family Medicine & Primary Care Review, 2017)
Background. Health is commonly regarded to be a social and individual value. It is perceived from the angle of multiple factors that determine health status. Objectives . Evaluation of the relationship between the value of health and the health behaviors declared by primary healthcare patients over 65 years of age. Material and methods. The study encompassed 505 patients of primary healthcare who were over 65 years of age. Those surveyed were asked to complete a questionnaire consisting of the Health Behavior Inventory (HBI) and Health Criteria List (HCL ) by Z. Juczyński. Results . The findings of the study demonstrate that in the evaluation of the health behaviors of the surveyed patients above 65 years of age, the average value of the HBI was 76.49 points. Having analyzed the separate categories of health behaviors, it has been reported that preventive behaviors and health practices were rated highest. These seniors paid the greatest attention to health in terms of property and condition. Health in terms of being a goal is treated as least important. Patients with a higher general level of health behaviors less frequently perceive health in the category of an outcome (p = 0.001). Conclusions . Seniors attach great significance to health understood as property or condition, which may explain their reluctant approach to this issue. The perception of health as an expected outcome is associated with a lower general rate of health behaviors.